2020
DOI: 10.9734/aprj/2020/v4i230083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saline Water Stress in the Presence of Silicon Foliar Application on Growth, Productivity and Chemical Constituents of Chia (Salvia hispanica L.) under Egyptian Conditions

Abstract: The pot experiment was carried out during two successive seasons (2016/2017 & 2017/2018) to study the effect of five levels of salinity and three levels of silicon (Si), as a foliar-spray application as well as their combinations on growth, productivity and chemical constituents of chia (Salvia hispanica L.) plants. Results showed that there was a negative relationship between vegetative growth measurements i.e., plant height, fresh weight and dry weight, flowering growth and yield parameters i.e., main in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Silva et al [52] studied the quantification of fatty acids in chia seed oils obtained with different solvents and reported αlinolenic (61.48-62.94%), linoleic (18.1-19.8%), oleic (6.92-6.87%), palmitic (9.13-9.95%), and stearic (2.92-2.99%). Moghith [53] identified 23 compounds in the fixed oil composition of chia, with the main components being α-linolenic acid (54.97-63.22%), linoleic acid (15.82-21.36%), oleic acid (6.19-15.86%), and palmitic acid (6.30-8.15%). Mohamed and Ghatas [40] reported that the main component in chia was α-linolenic acid (37.26-39.73%).It is worthy note that the quality of chia plant represented by crude fatty acids content improves when treated with bio-stimulants compared to the recommended mineral NPK fertilization [53].…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al [52] studied the quantification of fatty acids in chia seed oils obtained with different solvents and reported αlinolenic (61.48-62.94%), linoleic (18.1-19.8%), oleic (6.92-6.87%), palmitic (9.13-9.95%), and stearic (2.92-2.99%). Moghith [53] identified 23 compounds in the fixed oil composition of chia, with the main components being α-linolenic acid (54.97-63.22%), linoleic acid (15.82-21.36%), oleic acid (6.19-15.86%), and palmitic acid (6.30-8.15%). Mohamed and Ghatas [40] reported that the main component in chia was α-linolenic acid (37.26-39.73%).It is worthy note that the quality of chia plant represented by crude fatty acids content improves when treated with bio-stimulants compared to the recommended mineral NPK fertilization [53].…”
Section: Discussionmentioning
confidence: 99%
“…(2009) on of oregano plants, Jabeen and Ahmad (2011) on sunflower and safflower plants, Matin et al (2015) on Narcissus tazetta plants, Basiouny (2020) on Taxoduim disticum plant and Swietenia mahagoni plant, Ghatas and Mohamed (2020) demonstrated that, monopotassium phosphate with EM or phosphorein were the best for improving growth parameters of Oenothera biennis L. plant and Moghith et al (2020) reported that the maximum growth parameters of the chia (Salvia hispanica L.) plant have been shown to be preferred for cultivation under saline water irrigation at (0.68 dSm -1 ) and potassium silicate spray at 2000 ppm.…”
Section: Vegetative Growth Parametersmentioning
confidence: 98%
“…Ghatas and Mohamed (2020) mentioned that, monopotassium phosphate with EM or phosphorein were the best for improving chemical constituents of Oenothera biennis L. plant. Moghith et al (2020) It was shown that the combination therapy reported maximum N, P and K content values of the chia (Salvia hispanica L.) plant between 0.68 dSm -1 salinity concentration and 2000 ppm potassium silicate.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Additionally, Wang et al [7] reported that plant height, leaf freshness, and dry weight of maize seedlings were curtailed under salinity stress (150 mM and 300 mM NaCl concentration). Furthermore, Moghith et al [3] argued that elevating salinity levels lowered the vegetative growth of Salvia hispanica L. plants. In a study conducted in Cyprus, the authors discovered that the plant height of Lavandula angustifolia Mill.…”
Section: Vegetative Growth Characteristicsmentioning
confidence: 99%
“…Generally, the influences of salinity on plants are exhibited by a severe-to-moderate contraction in plant development and yield [2][3][4][5][6]. Plants can adapt to the adverse effects of salinity via both enzymatic and nonenzymatic antioxidant protective mechanisms to eliminate provoked ROS to protect plants against unfavorable influences of salinity.…”
Section: Introductionmentioning
confidence: 99%